2007
DOI: 10.1039/b711499k
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric organocatalytic reductions mediated by dihydropyridines

Abstract: Catalytic asymmetric reduction reactions have long been the preserve of the transition metal catalyst. Inspired by the myriad efficient enzyme-catalysed reduction reactions routine in biological systems, chemists have recently begun to design chiral metal-free organocatalysts that employ synthetic dihydropyridine NADH analogues as the hydride source with impressive results. Recent developments in this burgeoning field are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(47 citation statements)
references
References 164 publications
0
45
0
2
Order By: Relevance
“…[75] In this regard, it should not be forgotten that NADH (124), provides a metal-free hydrogenation in natural systems (Scheme 45) which bears some relation mechanistically to the metal-free reduction with the PH + /BH À systems. [76] In an early example, Sander et al showed that the strongly electrophilic carbene difluorovinylidene reacts directly with H 2 in an argon matrix at 20-30 K with practically no activation barrier to yield 1,1-difluoroethene (125; Scheme 46). [77] Formal insertion of examples of monoamino carbenes into the HÀH bond in solution were recently reported by Bertrand et al [35] (Scheme 18).…”
Section: Other Metal-free Catalytic Hydrogenation Reactionsmentioning
confidence: 98%
“…[75] In this regard, it should not be forgotten that NADH (124), provides a metal-free hydrogenation in natural systems (Scheme 45) which bears some relation mechanistically to the metal-free reduction with the PH + /BH À systems. [76] In an early example, Sander et al showed that the strongly electrophilic carbene difluorovinylidene reacts directly with H 2 in an argon matrix at 20-30 K with practically no activation barrier to yield 1,1-difluoroethene (125; Scheme 46). [77] Formal insertion of examples of monoamino carbenes into the HÀH bond in solution were recently reported by Bertrand et al [35] (Scheme 18).…”
Section: Other Metal-free Catalytic Hydrogenation Reactionsmentioning
confidence: 98%
“…[40][41][42][43] It has been observed that the formation of related dihydropyridines (e.g. 1,6-dihydronicotinamide and dihydroacridines) proceeds via sequential proton transfer (PT) and electron transfer (ET) steps.…”
Section: Scheme 1 Homogeneous Reduction Of Co2 To Methanol By 12-dimentioning
confidence: 99%
“…120,121 In-deed, since the discovery of NADPH in the 1930's, related dihydropyridine compounds have been studied, especially in connection with their HT to various substrates containing C=C, C=N and C=O groups. [40][41][42][43] HT to carbonyls is obviously of particular interest here: the reactant CO2 and its reduced intermediates formic acid (HCOOH) and formaldehyde (OCH2) leading to CH3OH formation all contain C=O groups susceptible to HT.…”
Section: Scheme 2 Formation Of Pyridinium Radical (Pyh 0 )mentioning
confidence: 99%
“…[1b,c] We recently found that transitionmetal-catalyzed allylic substitution reactions were compatible with asymmetric dearomatization processes for various aromatics such as indoles, pyrroles, and phenols. [2, 3] However, suitable aromatic compounds are limited to electron-rich nucleophiles, and electron-deficient aromatic compounds, such as pyridines and pyrazines, have not been explored yet.To date, asymmetric dearomatization reactions of pyridine derivatives have focused on asymmetric hydrogenations, [4] transfer hydrogenations, [5] and Reissert-type reactions.[6] In most cases, preactivation by N-acylation or alkylation to generate highly electrophilic pyridinium intermediates is required. The removal of the protecting group from the nitrogen atom is always essential at a later stage.…”
mentioning
confidence: 99%